The amylin dyshomeostasis hypothesis: small vessel-type ischemic stroke in the setting of type-2 diabetes mellitus - Despa, Florin (Stroke, 2021)
Recent histological analyses of human brains show that small-vessel type injuries in the setting of type-2 diabetes are colocalized with deposits of amylin, an amyloid-forming hormone secreted by the pancreas. Amylin inclusions are also identified in circulating red blood cells in persons with type-2 diabetes and stroke or cardiovascular disease. In laboratory models of type-2 diabetes, accumulation of aggregated amylin in blood and the cerebral microvasculature induces brain microhemorrhages and reduces cerebral blood flow leading to white matter ischemia and neurological deficits. At the cellular level, aggregated amylin causes cell membrane lipid peroxidation injury, downregulation of tight junction proteins and activation of pro-inflammatory signaling pathways which, in turn, induces macrophage activation and macrophage infiltration in vascular areas positive for amylin deposition. We review each step of this cascade based on experimental and clinical evidence, and propose the hypothesis that systemic amylin dyshomeostasis may underlie the disparity between glycemic control and stroke risk and may be a therapeutic target to reduce the risk of small-vessel ischemic stroke in patients with type-2 diabetes.